Challenges and future directions: From panacea to realisation - Charalambous, Andreas (My University, 2021)
The pace at which the evolution of technology has occurred within the healthcare context has been unprecedented; however, it has the potential to improve care. The introduction of technological solutions across the care continuum has revolutionised the way care is delivered; however introducing technological solutions and innovations also introduces unintended consequences and new challenges. This chapter emphasises on the challenges for implementing technological solutions in healthcare from an organisational perspective but also on those challenges that emerge following the utilisation of technology (e.g. from a user's perspective) in healthcare. Nevertheless, the technological solutions remain an asset in healthcare, and the development of existing solutions and the introduction of new ones are what we will experience in the future. The challenge is to have health policies in place that facilitate the implementation of technological solutions and making these more person-centric and user friendly without jeopardising ethical principles such as dignity as well as the safety and the privacy of the patient.
Keywords: Safety; User needs; Technology; Healthcare; Dignity; Privacy